Analisis Pengaruh Pembiayaan Murabahah, Pembiayaan Musyarakah Dan Sertifikat Bank Syariah (Sbs) Terhadap Profitabilitas Dengan Struktur Modal Sebagai Variabel Intervening Pada Perbankan Syariah Di Indonesia - Rosa, Desi Rosalina; Jeanne Aprilia (Risalah Iqtisadiyah: Journal of Sharia Economics, Sharia Economics Study Program, STEI Ar Risalah Sumatera Barat, 2022)
This study aims to determine how influential Murabahah financing, Musyarakah financing and Bank Syariah Certificates (SBS) are on profitability with the Mode Structure as an intervening variable in Islamic banking in Indonesia. The population in this study were Islamic banks in Indonesia from 2016 to 2020. While the research sample used was Secondary data on annual accounts of Islamic banks. Data collection techniques are using literature studies, documentation and internet research. Based on the results of this study: Murabahah financing has no effect on the profitability of Islamic banks. Musyarakah financing affects the profitability of Islamic banks. Bank Syariah Certificate (SBS) has an effect on the Profitability of Islamic Banks. Murabahah Financing, Musyarakah Financing and Bank Syariah Certificates (SBS) together have an effect on the Profitability of Islamic Banks. Capital structure is not able to mediate the effect of Murabahah Financing on the Profitability of Islamic Banks. The Capital Structure is not able to mediate Musyarakah Financing on the Profitability of Islamic Banks. Capital Structure is not able to mediate Bank Syariah Certificates (SBS) on the Profitability of Islamic Banks.